The influence of website characteristics on customer satisfaction and E-WOM in Indonesia - Alldila Nadhira Ayu Setyaning; Sahid Susilo Nugroho (Jurnal Siasat Bisnis, 2020)
There are many retailers that have developed their web stores and online forums with the purpose of getting closer to their customers. However, the significant growth of online stores makes the e-retailers face a challenge of fierce competition and survival. This study aims to analyse the relationship of website characteristics on customer satisfaction and positive E-WOM in internet shopping in Indonesia. The quantitative method is used to determine the relationships among variables. This research analysed 340 respondents who are born between 1984 to 2002 that have been experienced in buying the product from e-retailer in Indonesia at least once a month during the last year. To collect the data, this research used convenience sampling. The researcher used an online survey by Google Form to spread the questionnaires. Structural Equation Model with AMOS program was conducted to test the hypotheses. The results show that not all hypotheses are supported. The influence of shopping convenience on customer satisfaction and the influence of informative on customer satisfaction is positive but not significant. This research could help the e-retailers by providing digital marketing information, specifically, about attributes in website characteristics that could influence E-WOM through customer satisfaction.